2011
DOI: 10.1126/scitranslmed.3002001
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic DNA Triggers Inflammasome Activation in Keratinocytes in Psoriatic Lesions

Abstract: The proinflammatory cytokine interleukin-1β (IL-1β) plays a central role in the pathogenesis and the course of inflammatory skin diseases, including psoriasis. Posttranscriptional activation of IL-1β is mediated by inflammasomes; however, the mechanisms triggering IL-1β processing remain unknown. Recently, cytosolic DNA has been identified as a danger signal that activates inflammasomes containing the DNA sensor AIM2. In this study, we detected abundant cytosolic DNA and increased AIM2 expression in keratinocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
375
5
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(410 citation statements)
references
References 34 publications
21
375
5
4
Order By: Relevance
“…Patients with psoriasis express higher levels of LL-37 (Ong et al, 2002) compared with patients with atopic dermatitis. Dombrowski et al (2011) demonstrated that intracellular LL-37 serves as an anti-inflammatory agent by blocking the DNA-triggered formation of AIM2 inflammasomes in keratinocytes, inhibiting IL-1␤ release. However, several studies have shown that extracellular or endosomal LL-37 enhances TLR9 expression and function in keratinocytes, leading to increased IFN-␣/␤ production (Morizane et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with psoriasis express higher levels of LL-37 (Ong et al, 2002) compared with patients with atopic dermatitis. Dombrowski et al (2011) demonstrated that intracellular LL-37 serves as an anti-inflammatory agent by blocking the DNA-triggered formation of AIM2 inflammasomes in keratinocytes, inhibiting IL-1␤ release. However, several studies have shown that extracellular or endosomal LL-37 enhances TLR9 expression and function in keratinocytes, leading to increased IFN-␣/␤ production (Morizane et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reduced AIM2 expression in colorectal cancer is reportedly associated with poor outcome, suggesting a protective role for AIM2 here also [62]. In contrast elevated AIM2 levels and inflammasome activity have been reported in psoriatic lesions, possibly provoking this chronic autoimmune disease via sensing of self DNA [63]. Altered PYHIN1 and MNDA levels in a number of conditions have also been reported (Table 1).…”
Section: Disease Related Roles Of the Pyhin Proteinsmentioning
confidence: 94%
“…LL-37 is a human cathelicidin antimicrobial peptide that forms a complex with extracellular self-DNA, sequestering it and inhibiting the ability of DNA to induce IL-1b production via the AIM2 inflammasome. However, LL-37 promotes cellular uptake of self-DNA and while LL-37/self-DNA complexes do not appear to activate AIM2, they do initiate inflammatory cascades via TLR9 [63]. This highlights the difficulty in targeting a molecule which can exert effects via multiple PRRs.…”
Section: Therapeutic Approaches To Targeting Pyhin Proteinsmentioning
confidence: 99%
“…Interestingly, activation of an inflammasome has also been reported in nonmyeloid cells (33,34), which are the preferred host cells for many intracellular pathogens. For example, an infection of cervical epithelial cells by Chlamydia trachomatis, an intracellular pathogen, leads to activation of caspase-1 through the NLRP3 inflammasome (33).…”
Section: Introductionmentioning
confidence: 99%
“…The human AIM2 protein from the IFN-inducible p200-protein family senses cytoplasmic dsDNA (hereafter referred as DNA) in myeloid cells (35)(36)(37) and "primed" (treated with IFN-g and TNF-a) human keratinocytes (34). Upon sensing DNA, the AIM2 protein recruits an adaptor protein ASC to form the AIM2 inflammasome (31,(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%